2001
DOI: 10.1074/jbc.m105088200
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase Activity of Insect-derived Growth Factor Is Essential for Its Growth Factor Activity

Abstract: Insect-derived growth factor (IDGF) was originally isolated from conditioned medium of NIH-Sape-4 cells derived from flesh fly embryos. Here we demonstrated that IDGF has adenosine deaminase activity. The substrate specificity of IDGF was similar to that of the mammalian cytoplasmic adenosine deaminase. The adenosine deaminase activity of IDGF was shown to be indispensable for its growth factor activity toward NIHSape-4 cells. We found that there are specific binding sites for IDGF on the surface of NIH-Sape-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…A further protein enriched in bacteriocyte samples was ACYPI001365 (#214, 0.11%). Although annotated as "insectderived growth factor," the homolog of this protein has been reported to have adenosine deaminase activity in the fleshfly Sarcophaga peregrine (49), raising the possibility that this protein mediates the transformation of adenosine to inosine.…”
Section: Fig 2 Experimental and Bioinformatics Workflow Of The Protmentioning
confidence: 99%
“…A further protein enriched in bacteriocyte samples was ACYPI001365 (#214, 0.11%). Although annotated as "insectderived growth factor," the homolog of this protein has been reported to have adenosine deaminase activity in the fleshfly Sarcophaga peregrine (49), raising the possibility that this protein mediates the transformation of adenosine to inosine.…”
Section: Fig 2 Experimental and Bioinformatics Workflow Of The Protmentioning
confidence: 99%
“…The ADGF/ADA2 family proteins (3,14,15) were first described as growth factors in insects (16,17) and later were found to possess the ADA activity, which was shown to be essential for the growth factor activity (3,18,19). The physiological role is best described for the Drosophila homologue, ADGF-A (3,20).…”
mentioning
confidence: 98%
“…As we also found that ADA2 can bind to and modulate the affinity of ADRs, we hypothesized that the ADA2 binding to T cells is mediated by ADRs or an ADR-proteoglycan complex. Previously, the binding to the cell surface via unknown receptors was found for insects (17,18) and proposed for amphibian homologues (19), suggesting that this might be a common signaling mechanism for ADGF/ADA2 proteins that is complementary to or cooperating with the signaling via the enzymatic activity.…”
mentioning
confidence: 99%
“…Next, we examined the growth factor activities of Xl_ CECR1-1 and Xl_CECR1-2 in NIH-Sape-4 cells, as these cells are sensitive to various invertebrate ADGFs (1,3,10,11,15). Although both Xl_CECR1-1 and Xl_CECR1-2 showed growth factor activity, Xl_CECR1-1 displayed activity at lower concentrations than Xl_CECR1-2 ( Fig.…”
Section: Identification and Characterization Of X Laevis Cecr1 Cdnas-mentioning
confidence: 99%
“…ADA activity has been reported for some ADGF/CECRs (9 -14), including IDGF (3), where the K m , V max , and k cat values are comparable with those of mammalian cytoplasmic ADAs (21). As IDGF was originally identified as a growth factor in an embryonic cell line (1) and ADA activity was shown to be indispensable for growth factor activity (3), it is plausible that the ADGF/CECR1 family plays a role in cell proliferation during morphogenesis and organogenesis via its ADA activity.…”
mentioning
confidence: 99%